Fear conditioning in psychopaths: event-related potentials and peripheral measures - Rothemund, Yvonne; Flor, Herta (Biological psychology, 2012)
Aversive pavlovian delay conditioning was investigated in a sample of 11 criminal psychopaths as identified by using the Psychopathy Checklist-Revised and 11 matched healthy controls. A painful electric stimulus served as unconditioned stimulus and neutral faces as conditioned stimuli. Event-related potentials, startle response potentiation, skin conductance response, corrugator activity, and heart rate were assessed, along with valence, arousal, and contingency ratings of the CS and US. Compared to healthy controls, psychopathic subjects failed to differentiate between the CS+/CS− as shown by an absence of a conditioned response in startle potentiation and skin conductance measures. Through use of a fear-eliciting US, these data confirm previous findings of a deficient capacity to form associations between neutral and aversive events in psychopathy that appears unrelated to cognitive deficits and is consistent with hypothesized frontolimbic deficits in the disorder.